Spent coffee grounds as a sustainable coffee flavouring ingredient in muffins - Sina Breian Solberg; Svein Øivind Solberg (Exploration of Foods and Foodomics)
Aim: United Nations calls for actions to meet future challenges, and industries and governments need to look for new solutions. Coffee is one of the largest industries in the world, and spent coffee grounds (SCG) represents 50% of its waste. Sustainable ways to manage this waste are of interest. Research has shown that SCG is rich in dietary fibres and antioxidants, and we liked to examine if SCG could be used in flavouring muffins. The objectives were to investigate the viability of processing SCG through a comparison of different drying methods, to evaluate how SCG influences properties of baked goods and to investigate consumer acceptance of muffins with SCG. Methods: Three methods for drying SCG were used: oven drying, freeze drying, and vacuum drying. Muffins were baked with 10% milled and sieved SCG related to flour weight, and a control with 2.5% espresso powder. C-cell-, texture- and moisture analyses were conducted along with a sensory analysis. Results: The laboratory measurements showed that SCG powders were comparable to the control regarding textural parameters, except for the slice area parameter. The sensory analysis showed no clear difference in bitterness but a difference in graininess and coffee flavour. The least grainy was the control which also had the strongest coffee flavour. The vacuum dried was the grainiest and the freeze dried had the least coffee flavour. Ranking data showed the control in top and the vacuum dried bottom. Conclusions: SCG has the potential as flavouring coffee muffins but a finetuning in the processing and recipe development is needed to retrieve more coffee flavour without increasing bitterness or graininess.